An empirical investigation of news impact on stock market volatility during war and post-war periods in sri lanka - Peiris, T.U.I. (University of Jaffna, 2012)
This paper fits Exponential Generalized Auto-Regressive Conditional Heteroskedasticity (EGARCH) and Threshold GARCH (TGARCH) models to the daily closing All Share Price Index (ASPI) of Colombo Stock Exchange (CSE) for the War and Post-war Periods to recognize the leverage and news impact in CSE. The empirical results indicate that the news impact is symmetric and the leverage effect does not exist during the war periods. However, in the post-war period leverage effect exists and the news impact is asymmetric. During both these periods a positive returns shock to CSE produces lower volatility than a negative returns shock. Also the relationship between volatility and returns is negative for both the periods.
Keywords: Leverage; News Impact; Egarch; Tgarch